Comparative Study of the Internal Dynamic Failures of Grid-Connected Solar PVs: The Case of the Oman Power Network - Okedu, Kenneth E.; Al Ghaithi, Ahmed Sultan Salim (Frontiers in Energy Research, 2022)
Solar Photovoltaic (PV) offers hope toward environmental sustainability in terms of carbon and global heat reduction. The harvested energy from solar PV depends on the solar radiation, temperature of the cells, and the voltage generated in the PV modules. With the recent proliferation of solar PV projects in Oman, it is imperative to carry out new studies on the causes and effects of failures of these grid connected PVs, for effective and reliable performance. This study serves as a prototype to evaluate the performance of solar PV installations in Oman, considering the possible failures that may occur. These failures could lead to poor performance of the solar PV systems during operation. The performance analysis of a 6.2 MW grid-connected solar photovoltaic system in Muscat car parking, Oman is presented in this paper. The electrical parameters, and data analysis of the PV system were evaluated by monitoring the voltage, frequency, power factor, and total output power variables. The analysis of the PV performance was based on three internal dynamic failures; dust accumulation, inverter malfunction, and faulty protection schemes. When the solar PV cells were exposed to high percentage of contamination and dust, the plant performance dropped sharply to lower power generation by 43.5%. Furthermore, Inverters failure data analysis show that the average power generation degraded by 34%, and the average power generation degradation of 1% in the same period due to protection schemes failure. The results demonstrated that dust accumulation and inverter malfunction are the two major shortcomings that could lead to low power efficiency of solar PVs during operation.